COMPARATIVE ECOLOGICAL STUDY OF PHYTOPLANKTON OF BAKAR AND PHOOSNA LAKES-PAKISTAN (Biological Sciences - PJSIR, 2002)
A comparative ecological study of phytoplankton of Lake Bakar, district Sanghar and Lake Phoosna, district Badin  was  carried out during August, 1993 to July, 1996. A total of 78 species belonging to 33 genera of 5 classes (Bacillariophyceae, Chrysophyceae, Dinophyceae , Xanthophyceae and Euglenophyceae) were recorded. 12  species  were  common  in  both Lakes. 58 species were present in Lake Bakar and 8 in Lake Phoosna. The study showed that  the aquatic  environment  of Lake Bakar  is  qualitatively  much  better  as compared  to Lake Phoosna.